The evolution of constructivism (from a constructivist perspective) - Blanco, Christian; Cabrera, Andrés; Gaete, Tomás; Pinilla, Juan Pablo (MAD, 2010)
This article discusses the evolutionary conditions of constructivism on society, from Luhmann's social systems theory. First, we review some of the basic notions of the theory of social and cultural evolution, focusing on the concepts of variation, selection and stabilization of semantics in expectation structures. We suggest that these elements find empirical scenarios suitable for observation in scientific and philosophical communications, as well as in cultural productions. Our discussion leads to the question regarding the likeliness of stabilization of constructivism in expectations that operate in everyday life. We conclude with the hypothesis that constructivism -on its expressions on several systems- constitutes an evolutionary acquisition, as it allows the coupling of new and more complex communications in contemporary society.